Symptomatic lymphatic cysts after oncourological operations on the pelvic organs and influence of their anatomical localization on the clinical appearance - S. V. Kotov; A. О. Prostomolotov (Вестник урологии, 2020)
Introduction. Lymphatic cysts (LC) are the accumulation of free lymphatic fluid in a limited space (between tissues and organs), in the place where the lymphadenectomy was performed. They are the most frequent complications in pelvic oncourology. LC are divided into symptomatic and asymptomatic.Purpose of the study. To assess the influence of the anatomical localization of symptomatic lymphatic cysts (sLC) on the clinical appearance.Materials and methods. 203 radical prostatectomies (RPE) and 42 radical cystectomies (RC) were performed with pelvic lymph node dissection (PLND) in the N.I. Pirogov City Clinical Hospital № 1 from January 2017 to March 2020. Of 203 patients, 13 (6.4%) developed SLC, and of 42 patients, 6 (14.3%). All patients who developed complications underwent complex ultrasound studies and multispiral computed tomography (MSCT) of the retroperitoneal space, abdomen, and pelvic area to assess the localization and volume of the sLC.Results. Four anatomical localizations of the sLC can be distinguished after analyzing the clinical picture of 19 patients with sLC and comparing the obtained data with MSCT: paravasal-iliac, paravesical, prevesical, and pelvic-retroperitoneal. The frequency of paravasaliliac sLC was higher, they developed in 13 (68.5%) patients. The clinical picture included: pain in the pelvic area, lymphedema of the lower limb, body temperature ≥ 39.0 °C, due to LC infection and compression of the iliac vessels. Paravesical sLC were found in 2 (10.5%) patients. There was a failure of the urethrovesical anastomosis, according to retrograde cystography, due to displacement of the bladder. Prevesical sLC were found in 2 (10.5%) patients. Patients noted progressive urinary incontinence and pain above the pubic symphysis. Pelvic-retroperitoneal sLC was observed in 2 (10.5%) patients, with the clinical appearance of nagging pain in the lumbar region, body temperature ≥ 38.0 °C, due to ureteral compression and the development of obstructive pyelonephritis, as well as compression of the inferior vena cava by a lymphatic cyst. The repeated intervention was performed in 18 cases: percutaneous drainage of the LC under ultrasound guidance in 12 (63.2%) patients, laparoscopic marsupialization of the LC in 3 (15.7%) patients, an open technique in 3 (15.7%). In 1 patient (5.4%) the treatment was conservative.Conclusion. Symptomatic LC can be classified according to 4 anatomical locations, which define their clinical symptoms. Most sLC require reoperation.